2020
DOI: 10.3892/ol.2020.12213
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of serum miR‑1246/miR‑106b ratio in patients with esophageal squamous cell carcinoma

Abstract: The function of microRNAs (miRs) is associated with the development and progression of various malignancies, with miRs presenting stably in the serum. The current study assessed the role of miR-1246 and miR-106b in the serum of patients with esophageal squamous cell carcinoma (ESCC). A comprehensive microarray analysis of miR expression was performed using the serum of patients with ESCC, which were subsequently validated via reverse transcription-quantitative PCR. A total of 55 test samples were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Despite the continuous improvement in medical technology and comprehensive treatment, the prognosis of ESCC patients remains poor ( Yang et al, 2020a ; Wei et al, 2020 ). It is reported that the overall survival rate of ESCC is as high as 20–30%, and there is still much room for improvement because the 5-year survival rate of ESCC patients could rapidly increase to 80–90% if they were detected in the early stage and received the timely intervention ( Fitzmaurice et al, 2017 ; Hoshino et al, 2020 ). Unfortunately, since nearly half of early-stage ESCC patients were unlikely to show clinical symptoms, coupled with the lack of reliable noninvasive screening methods, more than 50% of ESCC patients were diagnosed at the advanced stages ( Ohashi et al, 2015 ; Kojima and Doi, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the continuous improvement in medical technology and comprehensive treatment, the prognosis of ESCC patients remains poor ( Yang et al, 2020a ; Wei et al, 2020 ). It is reported that the overall survival rate of ESCC is as high as 20–30%, and there is still much room for improvement because the 5-year survival rate of ESCC patients could rapidly increase to 80–90% if they were detected in the early stage and received the timely intervention ( Fitzmaurice et al, 2017 ; Hoshino et al, 2020 ). Unfortunately, since nearly half of early-stage ESCC patients were unlikely to show clinical symptoms, coupled with the lack of reliable noninvasive screening methods, more than 50% of ESCC patients were diagnosed at the advanced stages ( Ohashi et al, 2015 ; Kojima and Doi, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among 29 included studies [ 19 47 ], seven studies demonstrated the diagnostic performance of circulating miR-1246 in breast cancer [ 21 , 24 , 26 , 29 , 41 , 42 , 44 ], while four studies showed data for colorectal cancer [ 20 , 33 , 37 , 46 ], four others for hepatocellular carcinoma [ 23 , 31 , 32 , 43 ], and three for esophageal squamous cell carcinoma or pancreatic cancer [ 19 , 27 , 35 , 36 , 39 , 45 ] ( Table 1 ). Twenty-six out of 29 studies included healthy individuals as the control group, which did not avoid a case-control design and thus might introduce biases according to the QUADAS-2 revised tool ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Study Characteristics. Among 29 included studies , seven studies demonstrated the diagnostic performance of circulating miR-1246 in breast cancer [21,24,26,29,41,42,44], while four studies showed data for colorectal cancer [20,33,37,46], four others for hepatocellular carcinoma [23,31,32,43], and three for esophageal squamous cell carcinoma or pancreatic cancer [19,27,35,36,39,45] (Table 1). Twenty-six out of 29 studies included healthy 8…”
Section: Resultsmentioning
confidence: 99%
“…A six-miRNA signature of upregulated miR-106a, miR-18a, miR-20b, miR-486-5p, and miR-584 and downregulated miR-223-3p in ESCC was identified, which could correctly discriminate esophageal squamous cell carcinoma patients from healthy controls. Hoshino et al [51] assessed the role of miR-1246 and miR-106b in the serum of patients with esophageal squamous cell carcinoma. The results revealed that miR-1246 expression was significantly increased and miR-106b expression significantly decreased in each cohort.…”
Section: Esophageal Cancermentioning
confidence: 99%